Philanthrocapitalism and the Hidden Power of Big U.S. Foundations - Plank, Kerstin (Momentum Quarterly, 2017)
This paper seeks to discuss the modern concept known as philanthrocapitalism. By shedding light on the philanthropic commitment of American billionaires, it investigates how super-rich benefactors exercise power by investing in huge foundations. A critical examination of the current rise of philanthrocapitalism is presented first, followed by a discussion on how foundations can be used to gain and maintain power to advance personal and business interests. The aim is to present a critical investigation of benefactors’ approaches to philanthropy.